2008
DOI: 10.1002/hep.22170
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of urotensin II and its specific receptor antagonist palosuran in cirrhotic rats†

Abstract: In cirrhosis, splanchnic vasodilation contributes to portal hypertension, subsequent renal sodium retention, and formation of ascites. Urotensin II(U-II) is a constrictor of large conductive vessels. Conversely, it relaxes mesenteric vessels, decreases glomerular filtration, and increases renal sodium retention. In patients with cirrhosis, U-II plasma levels are increased. Thus, we investigated hemodynamic and renal effects of U-II and its receptor antagonist, palosuran, in cirrhotic bile duct-ligated rats (BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 46 publications
6
92
2
1
Order By: Relevance
“…Splanchnic vascular resistance was significantly decreased in weekly embolized rats compared to rats with only a single embolization (Fig 3e). This is in line with hemodynamic findings in portal hypertension [16,25]. There were no significant differences in the MAP (weekly embolization: 87.0 ± 13.2; single embolization: 96.2 ± 12.2; control: 91.0 ± 6.9) and in the cardiac output (weekly embolization: 19.0 ± 1.6; single embolization: 29.8 ± 5.3; control: 16.7 ± 4.1), respectively.…”
Section: Development Of Portal Hypertension In Nciph Ratssupporting
confidence: 92%
See 3 more Smart Citations
“…Splanchnic vascular resistance was significantly decreased in weekly embolized rats compared to rats with only a single embolization (Fig 3e). This is in line with hemodynamic findings in portal hypertension [16,25]. There were no significant differences in the MAP (weekly embolization: 87.0 ± 13.2; single embolization: 96.2 ± 12.2; control: 91.0 ± 6.9) and in the cardiac output (weekly embolization: 19.0 ± 1.6; single embolization: 29.8 ± 5.3; control: 16.7 ± 4.1), respectively.…”
Section: Development Of Portal Hypertension In Nciph Ratssupporting
confidence: 92%
“…Hemodynamic studies were performed under ketamine/xylazine anesthesia (78mg/kg / 12.5mg/kg i.p.) as previously described [14][15][16][17]. Rats were fasted overnight but allowed free access to water.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-localization experiments with UT (C4, arrow) and CD68 (C5, arrow) show that these cells were Kupffer cells (C6, arrow). Tribeka et al in a rat model of cirrhosis (20,21). In apparent variance with our data, Leifeld et al have shown by immunohistochemistry that there was no significant difference in UII/UT between cirrhotic and control liver.…”
Section: Discussioncontrasting
confidence: 77%